Fixed Asset Intensity, Leverage, Company Size and Sales Growth Against Tax Avoidance in Food and Beverage Manufacturing Companies: Intensitas Aset Tetap, Leverage, Ukuran Perusahaan dan Pertumbuhan Penjualan Terhadap Tax Avoidance pada Perusahaan Manufaktur Subsektor Makanan dan Minuman - Mafridah, Septa Dina; Ernandi, Herman (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the effect of fixed asset intensity, leverage, sales size and sales growth on tax avoidance in food and beverage manufacturing companies listed on the Indonesia Stock Exchange in 2015 – 2019. The research method used is quantitative method. The sample was determined based on the purposive sampling method and obtained a research sample of 30 issuers' financial statements. The sources used were secondary data in the form of financial reports and annual reports obtained from the Indonesia Stock Exchange website (www.idx.co.id). The data processing program uses the Statictical Product and Service Solution (SPSS) version 25 program.The data analysis method used was descriptive analysis and continued with requirements including normality test, multicollinearity test, heteroscedasticity test and autocorrelation test. The statistical method used to analyze the data using multiple linear regression analysis. Based on the results of multiple linear analysis test with a significant level of 5%, the results of this study concluded that the variable intensity of fixed assets and firm size had an effect on tax avoidance, while the variables of leverage and sales growth had no effect on tax avoidance.